El talento humano y su influencia en el Posicionamiento de mercado de la empresa megaproprinec de la ciudad de Babahoyo Provincia de Los Ríos - Castro Hernández, Lilian Estefanía (2015)
The present study was conducted to identify gaps in terms of the performance of human talent Megaproprinec City Babahoyo , which surveys allowed to obtain primary information and thus be able to solve these problems was applied. In Chapter I the part concerning the research objectives of this thesis will . In Chapter II the development of the framework where the research...